Unveiling Attitude and Motivation of English Education Students toward English - Hardianti, Meisela; Murtafi'ah, Banatul (Journal of English and Education (JEE), 2022)
English learning is often influenced by several aspects such as attitude and motivation. In fact, not all the students from the English Education Department have a positive attitude and motivation toward the major they are studying. While many studies have been conducted on attitude and motivation among secondary and university students, rarely have we seen a similar study for English Education Department students. Therefore, this study aims to determine English Education students’ attitudes and motivation in learning English. This was a survey study with 183 students participating in this study. This study used a modified version of AMTB (Attitude and Motivation Test Battery) from Gardner to collect the data. The recent version was adapted from Imsa-Ard (2020). There were 34 questions; the questionnaire was divided into five aspects (i.e., personal, emotional, educational, professional, and parental). The data were then analyzed by using SPSS and Microsoft Excel. The results show that English Education students have a positive attitude and motivation toward English. The overall results revealed that the English Education students in this study are highly motivated in the professional aspect. This implied that the professional atmosphere in these institutions should be maintained as it could boost students’ attitudes and motivation.